The Relationships between Family Support and Well Being among Patients with Breast Cancer on going Chemotherapy - พื้นทอง, ศุภลักษณ์; กสิผล, ทวีศักดิ์; ประเสริฐทรง, ชฎาภา (Journal of The Royal Thai Army Nurses, 2019)
The study was descriptive research. The purpose of research were to study level of well being, and to study the relationships between family support and well being of breast cancer patients who derived chemotherapy. The samples were breast cancer patients and mastectomy and treated with chemotherapy. A total of 71 samples were used in this study. The research instruments were the questionnaires about family support and well being. These questionnaires were created and adopted from chotika Pokhom, Chadapa Praserttong and et al. The data were analyzed by using descriptive statistics such as frequency percentage mean standard deviation and Pearson’s product moment of correlation coefficient. The research found that the side effects of chemotherapy were moderate level ( = 2.83, S.D. = 0.48). According to classified of the side effects, it was found that hair loss, anxiety and muscle pain were all symptoms at high level ( = 4.58, S.D. = 0.84, = 4.39, S.D. = 0.90, = 4.10, S.D. = 1.12 respectively). The sample have well being at high level ( = 3.82, S.D. = 0.39). There was significantly statistical correlation between the family support and well being of breast cancer patients who derived chemotherapy at .01 lavel (p<.01). The recommendations of this study should to develop family supportive program for breast cancer patients who derived chemotherapy.